Cimetidine suspension as adjuvant to energy restricted diet in treating obesity. Issue 6885 (24th April 1993) - Rasmussen, M H; Andersen, T; Breum, L; Gøtzsche, P C; Hilsted, J
Abstract : OBJECTIVE--To study the effect of cimetidine suspension compared with placebo suspension on weight loss in moderately obese patients taking a 5 MJ/day diet supplemented with dietary fibre. To determine the relation between the effectiveness of the blinding and weight loss. DESIGN--Randomised double blind study with an eight week parallel group phase and a subsequent eight week crossover or continuation phase. SETTING--Outpatient clinic. SUBJECTS--60 patients (51 women) aged 18-60. MAIN OUTCOME MEASURE--Weight loss. RESULTS--After eight weeks of treatment the mean weight loss in the cimetidine group (5.7 kg) was similar to that of the placebo group (5.9 kg; p = 0.78, 95% confidence interval -2.0 to 1.5 kg). Body mass index, waist and hip measurements, waist-hip ratio, and systolic and diastolic blood pressures decreased similarly in the two groups. No association was found between weight loss and the patients' ability to guess if they were being given drug or placebo. Correct guesses of current drug were more prevalent than expected by chance (25/37 correct, p = 0.05 for the parallel group phase; 26/30, p = 0.0001 for the crossover phase). CONCLUSIONS--Cimetidine had no effect on weight loss in moderately obese patients. The study underlines the potential problem that blinding of patients to treatment can be compromised.